ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA BERDASARKAN TAHAPAN NEWMAN BESERTA BENTUK SCAFFOLDING YANG DIBERIKAN - Fatahillah, Arif; Wati, Yuli Fajar; Susanto, Susanto (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research aims to analyze students error types in solving contextual mathematics problem based on Newman’s error analysis and scaffolding form that’s given to the eight students of Darul Hikmah Junior High School Jember. Instruments that were used in this research are contextual mathematical problem, interview guide, scaffolding guide, and validation sheet. The coeficient validity test is 4,81 and the coeficient validity interview guide is 4,75, so that the criteria of validity research instrumen is valid. Error types student’s according to Newman consists of reading error, comprehension error, transformation error, process skill error, and encoding error. Based on students’ errors, the highest error percentage is comprehension error that's 70,01%, and the lowest error percentage is reading error that’s 20,77%. Generally, the cause of students’ errors is they are not accustomed to solve contextual problems. Scaffolding is a form of help that’s given by the teacher to the students to overcome students’ difficulties when doing a task that can’t be finished by students. Scaffolding that was used in this research refers to Anghileri’s scaffolding level. In scaffolding level 1 (Enviromental Provisions), scaffolding that’s given to students is preparing the learning environment by explaining a little material about Arithmetic Operation Sub Subject of Fraction and giving contextual mathematical problem. Scaffolding that’s given to students with reading error and comprehension error is at level 2 that are reviewing, restructuring, and explaining. Scaffolding that’s given to students with transformation error at level 2 that are reviewing, restructuring, and explaining and level 3 that’s developing conceptual thinking. Scaffolding that’s given to students with process skill error is at level 2 that are reviewing, restructuring, and explaining. Scaffolding that’s given to students with encoding error is at level 2 that are reviewing. Key Words: Newman’s Error Analysis, Scaffolding, and Arithmetic Operation Sub Subject of Fraction